Profound molecular response with ponatinib in chronic phase of chronic myeloid leukemia with resistance to imatinib and dasatinib: Case report and review of the literature - Díaz, Carol (2022)
We report the case of a woman who at the age of 54 years was diagnosed with chronic myeloid leukemia in chronic phase; she began treatment with a first-generation tyrosine kinase inhibitor, and evidenced failure due to the absence of a hematological and cytogenetic response. Despite changing treatment to a second-generation tyrosine kinase inhibitor (dasatinib), it was not possible to achieve optimal levels of response, documenting positivity for the T315I mutation in the ABL domain of the deregulated BCR/ABL tyrosine kinase, compared to ponatinib, the only drug that shows activity. After starting treatment with ponatinib, optimal levels of cytogenetic and molecular response were evidenced, as well as an adequate quality of life for the patient.